PMR BERBASIS WML PADA LUAS DAN VOLUME KERUCUT (WEBSITE-MOBILE-BASED LEARNING OF REALISTIC MATHEMATICS EDUCATION (RME) ON THE MEASUREMENT OF THE AREAN AND VOLUME OF CONE) - Abd. Rohman S; Tri Susilaningtyas (FKIP Universitas Islam Jember, 2013)
Despite of its misuse, such as ethical disobidience by the students in the classroom during the teaching and learning process, handphone (HP) is an urgent device in education that facilitates learning.The problem of the research is “How is the implementation of Website Mobile Learning by Using HP to develop Realistics Mathematics Learning on the measurement of the area and the volume of cone?’. The long-term objective of the research is to develop HP as the media of realistics mathematics learning on the measurement of the area and the volume of cone. While the short-term objective of this research is (1) to create website program on the measurement of the area and the volume of cone that can be accessed through HP. (2) The occurence of the development of Realistics Mathematics Education on the measurement of the area and the volume of cone.In general, this research is an attempt to develop a software application on the measurement of the area and the volume of cone for Website Mobile Learning. It used Developmental research in nature The steps of this research include pre-liminary study covering observation and literary study, system analysis, system design, system development, system testing, system verification and validation, sytem revising and review, system tral, and output analysis.Keyword: Realistic Mathematics Education, Wapstie Mobile Learning, Arean And Volume Of Cone